If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 19 = 0 Reorder the terms: 19 + 10x = 0 Solving 19 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 10x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + 10x = 0 + -19 10x = 0 + -19 Combine like terms: 0 + -19 = -19 10x = -19 Divide each side by '10'. x = -1.9 Simplifying x = -1.9
| 2+5=10+2 | | F(x)=(2x-3)(4x-5) | | 16m-24m+36=0 | | 7x-7x-x=14 | | 0=0.98b+0.02b | | 0=-7x+4(3x-6) | | -16t^2+vt+s=0 | | 2h-0.1=6.25 | | 7x+1=4-2x | | sin(x)*cos(4x)=sin(5x) | | 20x+30y=412.5 | | -42+10x=6x+70 | | 2x-5=61 | | z+7=4 | | 4.6z-6=3.6z-6 | | 21-4x=-27 | | 8x-4x+3x=7x+x+14 | | X^2=aX^2+25b^2-10ab | | 2x+12+9x-27=12+24 | | 8sqrtx=x+15 | | 2(4x+10)=8x+10 | | 7-12=-2 | | 7.6x+1=6.6x | | 3(3w-6)=8 | | x+6(x-1)=7 | | 5*5*8*8*5*5= | | -129+x=131+11x | | -3x-14=-8x+13 | | 26-b=39-9 | | 2x+1+x-3+44=180 | | -6+-2x=29+3x | | 63+5u=14u |